2001
DOI: 10.1007/bf02988239
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-MIBI SPECT in small cell lung cancer patients before chemotherapy and after unresponsive chemotherapy

Abstract: We evaluated the accumulation of 99mTc-MIBI in small cell lung cancer patients before chemotherapy and after unresponsive chemotherapy. The pre-chemotherapeutic group included 22 newly diagnosed patients. These patients underwent a 99mTc-MIBI SPECT study before starting chemotherapy. After chemotherapy, based on changes in tumor size, three different patterns of response (complete remission: CR, partial remission: PR and no change: NC) were defined. The post-chemotherapeutic group included 11 patients after ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…These include initial uptake of 99m Tc-MIBI, delayed retention, percentage washout, and retention index. The best parameter for predicting the response to chemotherapy was the degree of initial 99m Tc-MIBI uptake by the tumor, seen in 7 of the 8 studies included (7,9,(11)(12)(13)(14)(15). In all of these studies, lung cancer patients who had less 99m Tc-MIBI uptake were less likely to respond to chemotherapy than those who had more uptake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include initial uptake of 99m Tc-MIBI, delayed retention, percentage washout, and retention index. The best parameter for predicting the response to chemotherapy was the degree of initial 99m Tc-MIBI uptake by the tumor, seen in 7 of the 8 studies included (7,9,(11)(12)(13)(14)(15). In all of these studies, lung cancer patients who had less 99m Tc-MIBI uptake were less likely to respond to chemotherapy than those who had more uptake.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 99m Tc-MIBI is a transport substance recognized by multidrug resistance (MDR)-related P glycoprotein (P-gp) and that tumor cell accumulation is enhanced by inhibition of the efflux transport function (7). These results provided the basis for clinical studies that investigated the role of 99m Tc-MIBI in predicting the response to chemotherapy in patients with lung cancer (8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 90%
“…The overall sensitivity of 99m Tc-Sestamibi in identifying responders to chemotherapy is 94% with the specificity of 90%, and the accuracy of 92% [57][58][59][60][61][62][63][64]. Although the number of published studies examining the effectiveness of 99m Tc-Sestamibi in preselecting lung cancer patients before chemotherapy is limited, it can be concluded that when 99m Tc-Sestamibi is used, it is very effective in differentiating responders from non-responder patients [6].…”
Section: Lung Cancersmentioning
confidence: 98%
“…Therefore, suppression of MDR via irradiation can be effectively investigated using the change in intracellular uptake of MIBI. Furthermore, based on this pharmacokinetic property, a number of clinical studies have reported that MIBI imaging may be used to obtain an early estimate of the therapeutic response to chemotherapy by assessing the cancer MDR (16)(17)(18)(19)(20)(21)(22)(23). In this study, MIBI was used to investigate the response of MDR in H1299/wtp53 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…MIBI, as a substrate for Pgp and MRP1, has been shown to have similar pharmacokinetics to chemotherapeutic agents such as doxorubicin (12)(13)(14)(15). Therefore, there are a number of clinical research reports assessing the utility of MIBI in predicting the chemotherapeutic response in non-small cell lung cancer (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%